Mobile telephony, social networks and credit access: Evidence from MSMEs in Kenya - Idi Jackson Mdoe; George Kariuki Kinyanjui (Cogent Economics & Finance, 2018)
Access to credit by micro, small and medium enterprises is key for growth and employment. However, it is hindered by information asymmetry. We investigated the effect of mobile telephony and social networks (group networks) on the probability of access to credit by Micro, Small and Medium enterprises in Kenya. Our analysis employed cross-sectional data, the 2016 FinAccess Household Survey infographics sheet. The analysis assumed a limited dependent variable modelling. Our analysis revealed that micro-, small- and medium-sized enterprises with owners who currently have mobile banking, mobile money and group participation, respectively, have 8.8, 6.05 and 1.97 percentage points higher chance of receiving formal credit. In terms of informal credit, the analysis revealed that below five groups participation in an extra group by the MSME owner increases the probability of accessing informal credit by 6.26 percentage points. As policy measures, our analysis implies that owners of MSMEs should participate in groups and take up mobile money and banking to further their MSMEs chances of accessing formal and informal credit. In addition, the findings imply that money lenders should create strategies to tap MSMEs reputation created by groups and mobile telephony.
Keywords: L14; 330; Micro small and medium enterprises; mobile telephony and social networks